2006
DOI: 10.1002/rcm.2344
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization tandem mass spectrometric analysis of fragmentation patterns of dithiocarbamate derivatives

Abstract: 722 Letter to the Editor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Alternatively, the cleavage of the C-S bond initiated by the bromide attack on the dithio bond afforded 5D at m/z 409 consistent with previous reports. [27,28] The lone electron pair on the amide nitrogen of 4D attacked the a-carbon of the ammonium nitrogen, followed by the elimination of dimethylamine which transformed the piperazinium ring to the aza-cyclopropane derivative 7D at m/z 460 (identified by MS 3 of 4D, Fig. 1(c)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the cleavage of the C-S bond initiated by the bromide attack on the dithio bond afforded 5D at m/z 409 consistent with previous reports. [27,28] The lone electron pair on the amide nitrogen of 4D attacked the a-carbon of the ammonium nitrogen, followed by the elimination of dimethylamine which transformed the piperazinium ring to the aza-cyclopropane derivative 7D at m/z 460 (identified by MS 3 of 4D, Fig. 1(c)).…”
Section: Resultsmentioning
confidence: 99%
“…The conventional analytical studies were focused on rapid identification of the minor active components to evaluate their non‐residual contaminations of food and feed samples; the mass spectrometric behavior of dithiocarbamate compounds was seldom reported in the literature. In view of its ability to provide molecular weight and abundant structural information, mass spectrometry has been employed in the identification and structural characterization of thioesters by electron ionization (EI) and later by electrospray ionization (ESI) 25–28. During the course of studying dithiocarbamates, we found that these compounds had both antitumor29 and analgesic activities 24.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MS 3 spectrum of the ion at m / z 296 yielded only one ion at m / z 238 and the MS 3 spectrum of m / z 143 resulted in ions at m / z 109 and 97. The fragmentation of protonated TM208 has already been elucidated by Hou et al ., as shown in Scheme 10, 11. These ions were subsequently used as diagnostic product ions for the tentative and definite identification of the nine unknown metabolites whose product ion spectra contained one or more of the same ions.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, studies of dithiocarbamate derivatives have usually focused on their pharmaceutical activity,2–6 with a few papers reporting their mass spectrometric behavior 7. We have previously determined the mass spectral fragmentation of dispirocyclopiperazinium structures,8, 9 and of some dithiocarbamate derivatives10, 11 synthesized in our laboratory, including TM208, using electrospray ionization multi‐stage mass spectrometry (ESI‐MS n ).…”
mentioning
confidence: 99%